Division Learning Challenges: Error Analysis of Elementary Students in Solving Merdeka Curriculum Assessment - Jagadianti, Gurit Wulan (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2025)
The aim of this study was to analyze the errors made by elementary school students in learning division in a public elementary school in Bojonegoro Regency. This research is classified as qualitative research employing descriptive methods. Data were collected from 29 fourth-grade students. The data were analyzed using Newman's Error Analysis. The results showed that students made errors in applying multiplication rules or subtraction rules in division problems. The majority of students' errors occurred in comprehension errors, transformation errors, and process skill errors. These errors highlight the need to focus on understanding the underlying mathematical process skills so that students can not only answer questions correctly but also apply the correct steps to solve math problems accurately. Therefore, identifying these errors is crucial to prevent the accumulation of mistakes or misunderstandings that can persist to higher education levels. Thus, it is important to provide further assistance to students in understanding and solving math problems and to build a strong foundation to ensure correct mathematical understanding from an early age in elementary school.